Programa EducaSostenible en directivos y docentes para mejorar la gestión en huella ecológica en la Institución Educativa Pública N° 60756 Claverito 2024 - Flores Tapullima, Lidia Gudelia (2025)
The primary objective of this study was to evaluate the effect of the EducaSostenible program on administrators and teachers, aiming to improve ecological footprint management at Public Educational Institution N°60756 Claverito in 2024. An evaluative research approach was employed, featuring a field study with a longitudinal, univariable, and quasi-experimental design, including both experimental and control groups. The study population consisted of 40 secondary-level administrators and teachers from the institution, with the sample size matching the population. Data collection was conducted using a survey through a written performance test, which had been previously validated by experts. The findings indicated that the EducaSostenible program was highly effective in enhancing ecological footprint management, as evidenced by a decrease in the percentage of participants at a good management level (from 67.5% to 0.0%) and an increase to a very good level (from 32.5% to 100.0%). Inferential analysis confirmed that the program's implementation significantly improved ecological footprint management, thereby validating the study's primary hypothesis.